O espírito do pastor: a espiritualidade inaciana no ministério do Papa Francisco - Ribeiro, Célia Maria (2018)
This work introduces Pope Francis ministry in a different light, an approach which has not been usually adopted, so far: Ignatian spirituality. From the start, it narrates Jorge Mario Bergoglio’s spiritual and intellectual backgrounds, which were firstly incorporated from his own family and further developed when he joined in the Society of Jesus. His trajectory as a clergyman highlights his struggles with his fellow brothers in his religious congregation, where he experienced both setbacks and advancements, especially, when we consider the Latin America historical context at the time, during which Argentina, where he was born and raised, was under a military dictatorship. Nevertheless, in spite of all the political tensions, his decisions always go in the direction of pastoral work and spiritual discernment. Following that, this work highlights the Second Vatican Council major influence over the Church new policies in our contemporary cultural scenario, a context full of challenges which were long felt in the successive Church crisis. This was an important aspect for Pope Benedict XVI resignation, which is also assessed in this work, a resignation that was followed by the conclave ending up in the election of the first Jesuit Pope. The circumstances for his choice and the facts triggered by the new Bishop of Rome, beginning with his decision to be called “Francis” and advancing to the traits of his Petrine ministry, are taken into account, especially in the light of Ignatian spirituality, when references to time, places and people are underlined. Nevertheless, it is a work that introduces Pope Francis inner language in the context of his outspoken life